THE REPRODUCTIVE CYCLE OF PUNTIUS BINOTATUS ON THE MIDDLE OF THE RAINING SEASON - Mujtahidah, Tholibah; Marsoedi, Marsoedi; Widodo, Maheno Sri (xxxx-xxxx)
Spotted barb (Puntius binotatus) is one of tropical fish in Indonesia freshwater, which has high economic value. To maintain the stock in nature, information about the reproduction cycle in the mid raining season is required for conservation so that we can control the catch of spotted barb. This study aimed to examine the effect of raining season on GMS, GSI and GI?s male and female. Observation methods were used as a tool to collect the data. The result of the research showed that a variety of GMS, GSI and GI?s male and female. Quantity of oocyte primer 423; 664; 480; 380; meanwhile that quantity of oosite secondary oocyte 73; 172; 411; 230. Result of water quality measured in the river as temperature 28-30oC, pH 6,8-7 and Dissolved Oxygen (DO) 3-3,4 ppm. The gonad weightgreatly influenced the rate of GMS, GSI, and GI in determining fish reproductionwas interrelated and directly proportional. Increasing of GMSwas affected by the increasing value of GSI and similarly the GI value which is directly proportional with increasing of GSI and GMS. The reproductive cycle of gonadal maturity spotted barb increased during themid rainy season.